O feminino na fotografia de arte: construindo fabulações a partir de autorretratos - Vilela, Mariana Queiroz (2025)
The aim of this dissertation is to analyze and test the concept of self-portrait, based on recent discussions surrounding the imagistic fabulations of women. The research corpora are based on the work of Kimiko Yoshida, a Japanese artist based in France, who uses self-portrait not only to represent her own image but to problematize stereotypical representations of women. In addition, the dissertation presents conceptual photographs created by me as part of the research, which point to female representations, using the notion of corpomídia (Katz; Greiner) as a starting point to explore the migratory processes of women like Yoshida and her fabulatory strategies to give visibility to the political issues embedded in visual narratives. The theoretical foundation also includes studies by authors who analyze the historiography of feminism, with a focus on representations of women (Haraway, Butler, Federici e Rago)